PostgreSQL 13 Cookbook - Kumar, Vallarapu (Packt Publishing, 2021)
Get to grips with building reliable, scalable, and maintainable database solutions for enterprises and production databases Key Features Implement PostgreSQL 13 features to perform end-to-end modern database management Design, manage, and build enterprise database solutions using a unique recipe-based approach Solve common and not-so-common challenges faced while working to achieve optimal database performance Book Description PostgreSQL has become the most advanced open source database on the market. This book follows a step-by-step approach, guiding you effectively in deploying PostgreSQL in production environments. The book starts with an introduction to PostgreSQL and its architecture. You'll cover common and not-so-common challenges faced while designing and managing the database. Next, the book focuses on backup and recovery strategies to ensure your database is steady and achieves optimal performance. Throughout the book, you'll address key challenges such as maintaining reliability, data integrity, a fault-tolerant environment, a robust feature set, extensibility, consistency, and authentication. Moving ahead, you'll learn how to manage a PostgreSQL cluster and explore replication features for high availability. Later chapters will assist you in building a secure PostgreSQL server, along with covering recipes for encrypting data in motion and data at rest. Finally, you'll not only discover how to tune your database for optimal performance but also understand ways to monitor and manage maintenance activities, before learning how to perform PostgreSQL upgrades during downtime. By the end of this book, you'll be well-versed with the essential PostgreSQL 13 features to build enterprise relational databases. What you will learn Understand logical and physical backups in Postgres Demonstrate the different types of replication methods possible with PostgreSQL today Set up a high availability cluster that provides seamless automatic failover for applications Secure a PostgreSQL encryption through authentication, authorization, and auditing Analyze the live and historic activity of a PostgreSQL server Understand how to monitor critical services in Postgres 13 Manage maintenance activities and performance tuning of a PostgreSQL cluster Who this book is for This PostgreSQL book is for database architects, database developers and administrators, or anyone who wants to become well-versed with PostgreSQL 13 features to plan, manage, and design effic ...